Training techniques to improve fatigue resistance and enhance endurance performance - Hawley, J. A.; Myburgh, K. M.; Noakes, T. D.; Dennis, S. C. (Journal of Sports Sciences, 1997)
Despite their best efforts, sports scientists have found it difficult to persuade elite athletes to experiment with their training regimens. Thus, until recently, exercise physiologists have had limited impact on the training practices of successful athletes, with most of the innovations in the training patterns of the best athletes coming from the empirical observations of top-level coaches. One form of training recognized by sports scientists and used by athletes for several decades is interval/transition training. Such training consists of a number of exercise bouts alternated with short rest intervals of more slowly paced activity and is thought to improve the fatigue resistance of the active muscles by exposing them to sustained, high-intensity exercise at the athlete's maximal steady-state pace. Few scientific studies, however, have examined the effects of transition training on the performances of competitive athletes. This paper identifies the physiological factors associated with successful endurance performance, and summarizes the results of a series of investigations on competitive endurance cyclists which examined the time-course of changes in performance in response to a ustained, high-intensity interval training programme.